We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
415
3
avatar

f(x)=e^x-1+2x-3

and the question is 

inverted function of x (f^-1(x))=0

please answer with steps

 Jul 9, 2015

Best Answer 

 #3
avatar+102763 
+5

hi anon,

This is an inverse function question                   (Factorials are something completely different)

 Jul 11, 2015
 #1
avatar+102763 
+5

 

$$\\f(x)=e^x-1+2x-3\\\\
Let\;\; y=f(x)\\
y=e^x-1+2x-3\\
y=e^x+2x-4\\
Domain\;\;x\in R \;\;and \;\; range\;\;y\in R\\
$and both x and y are both mapped 1 to 1 to the other$\\
$So it is ok for me to just going to swap x and y over$\\
$the inverse function is $\\
x=e^y+2y-4\\
If \;\;y=0\;\; then\;\; x=e^0+2*0-4=1-4=-3$$

 

 $$\\f^{-1}(x)=0 \qquad when \qquad x=-3$$

 

Here is the graph

 

https://www.desmos.com/calculator/lb12iqyjf0

 Jul 10, 2015
 #2
avatar
+5

Thanks a lot.Now I know how to solve equations with inverted factorial.I wish you the best!

 Jul 10, 2015
 #3
avatar+102763 
+5
Best Answer

hi anon,

This is an inverse function question                   (Factorials are something completely different)

Melody Jul 11, 2015

17 Online Users

avatar